Elevated CO2 improves phosphorus nutrition and growth of citrate‐secreting wheat when grown under adequate phosphorus supply on an Al3+‐toxic soil. (11th August 2022) - Dong, Jinlong; Delhaize, Emmanuel; Hunt, James; Armstrong, Roger; Tang, Caixian
Abstract: BACKGROUND: Understanding how climate change affects the phosphorus (P) nutrition of crops grown on acid soils is important in optimizing the management of P, and to secure future food production on these soils. This study assessed the impact of elevated CO2 (eCO2 ) on the P nutrition of wheat ( Triticum aestivum ) grown on Al 3+ ‐toxic and P‐deficient soils or in hydroponics. The aluminium‐resistant near‐isogenic wheat lines EGA‐Burke (malate efflux only) and EGA‐Burke TaMATE1B (malate and citrate efflux) were grown under ambient (400 μmol mol −1 ) and elevated CO2 (800 μmol mol −1 ) in growth chambers for 4–6 weeks. RESULTS: Elevated CO2 enhanced shoot growth and total P uptake of both lines at P rates >250 mg kg −1, which was associated with improved root biomass allocation and thus increased root growth, but these effects were not apparent at lower P rates. Elevated CO2 decreased specific P uptake (P uptake per unit root length) at P supply >250 mg kg −1, but did not significantly affect external or internal P requirements. This effect on the specific P uptake was less for EGA‐Burke TaMATE1B than for EGA‐Burke, possibly due to the increased citrate efflux and decreased Al concentration in root tips of EGA‐Burke TaMATE1B . Compared to EGA ‐ Burke, citrate‐exuding EGA ‐ Burke TaMATE1B had greater shoot P concentration and greater specific P uptake. CONCLUSION: Elevated CO2 improved root growth, and thus total P uptake and plant production of both lines when high P alleviated Al 3+ toxicity and improved P nutrition in acid soils. The decreased P uptake efficiency under eCO2 was less for EGA ‐ Burke TaMATE1B than EGA‐Burke . © 2022 Society of Chemical Industry.